Myeloperoxidase -463A variant reduces benzo[a]pyrene diol epoxide DNA adducts in skin of coal tar treated patients - Rojas, Margarita; Bartsch, Helmut (Carcinogenesis, 2001)
The skin of atopic dermatitis patients provides an excellent model to study the role of inflammation in benzo[a]pyrene (BaP) activation, since these individuals are often topically treated with ointments containing high concentrations of BaP. In this study we have determined, by HPLC with fluorescence detection, the BaP diol epoxide (BPDE)-DNA adduct levels in human skin after topical treatment with coal tar and their modulation by the -463G→A myeloperoxidase (MPO) polymorphism, which reduces MPO mRNA expression. BPDE-DNA adduct levels were 2.2 and 14.2 adducts/108 nt for MPO-463AA/AG and -463GG, respectively. The predominant BaP tetrol observed was tetrol I-1, which is derived after hydrolysis of the anti-BPDE-DNA adduct. The tetrol I-1/II-2 ratio, corresponding to the anti/syn ratio, was 6.7. The 32P-post-labeling assay was also performed and thin layer chromatograms showed a major spot with a chromatographic location corresponding to BPDE-DNA. The mean values of the BPDE-DNA adduct spots were 3.8 ± 2.4 per 108 nt for MPO-463AA/AG (n = 3) and 18.4 ± 11.0 per 108 nt for MPO-463GG (n = 7), respectively (P = 0.03). One individual with the homozygous mutant genotype (-463AA) even had a 13-fold lower adduct level (1.4 per 108 nt) as compared to MPO-463GG subjects. In conclusion, these data show for the first time: (i) the in vivo formation of BPDE-DNA adducts in human skin treated with coal tar; (ii) that the MPO-463AA/AG genotype reduced BPDE-DNA adduct levels in human skin.